An ion battery separator, a preparation method thereof and application thereof
Patent Information
- Application Number
- CN202310918782.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-07-25
AI Technical Summary
In existing metal halide-graphite intercalation compound materials, halide ions shuttle through the electrolyte, causing the diaphragm to yellow and its electrochemical stability to deteriorate, which seriously affects the cycle performance.
A slurry of a specific composition, including halogen-fixing materials, binders, dispersants, and wetting agents, is applied to a base film. By controlling the coating thickness and baking temperature, a coating is formed to fix halides and halide ions, preventing them from traversing the electrolyte.
It effectively prevents damage to the base film from halide ions and other side reactions, improves the cycle performance of the negative electrode, maintains electrochemical stability and thermal shrinkage, and is suitable for large-scale industrial production.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, and in particular relates to an ion battery separator, its preparation method and application. Background Technology
[0002] With the development of the new energy industry, lithium-ion batteries, which have higher energy density and are more environmentally friendly, are gradually replacing traditional nickel-cadmium and lead-acid batteries. As the penetration rate of lithium-ion batteries increases, the demand for improving battery energy density is also rising. Currently, the commonly used lithium battery anode is still graphite, but graphite's theoretical specific capacity is only 372 mAh / g, making it difficult to further increase energy density. Although high-capacity anodes such as silicon-carbon have emerged on the market, their development is limited by factors such as expansion, cost, and safety. Compared with other new anode materials, graphite-based anode materials are still considered the safest. Among them, metal halide-graphite intercalation compounds (such as ferric chloride-graphite intercalation compounds, FeCl3-GIC) are considered the most promising materials to replace graphite anodes.
[0003] Metal halide-graphite intercalated compounds possess lithium storage specific capacities exceeding 1371 mAh / g. However, the easy solubility of metal halides in electrolytes leads to halide ion shuttle movement within the electrolyte, severely impacting the cycling performance of these compounds. Existing technologies primarily improve halide ion shuttle movement in electrolytes through material preparation, such as introducing epoxy groups to enhance the chemical anchoring of FeCl3 in the graphite matrix or introducing Fe2O3 nanomolecules via microwaves to enhance the chemical adsorption of FeCl3, thereby reducing Cl- ion flow. - While electrolyte ion transport can improve battery cycle performance to some extent, it only improves the material preparation level and does not improve the separator (the membrane between the positive and negative electrodes). A considerable number of halide ions still transport through the electrolyte, causing the separator to yellow and its electrochemical stability to deteriorate. As a result, its cycle performance is still significantly lower than that of traditional graphite. Summary of the Invention
[0004] This invention provides an ion battery separator, its preparation method, and its application, aiming to solve the problems of halide ions shuttling in the electrolyte in existing metal halide-graphite intercalated compound materials, which leads to yellowing of the separator, poor electrochemical stability, and serious impact on the cycle performance of metal halide-graphite intercalated compound materials.
[0005] To achieve the above objectives, in one aspect, embodiments of the present invention provide a method for preparing an ion battery separator, comprising the following steps:
[0006] S01. Mix 15%–45% of a solid mixture with 55%–85% of water to obtain a slurry; the solid mixture comprises, based on 100% by mass, the following components: 90%–96% solid material, 3%–8% binder, 0.2%–1% dispersant, and 0.2%–1% wetting agent; the percentages are by mass.
[0007] S02. The slurry from step S01 is applied to the base membrane and baked to obtain the ion battery separator.
[0008] In a preferred embodiment, in step S01,
[0009] The solid mixture is preferably mixed at 500 rpm to 1000 rpm for 20 min to 40 min.
[0010] The pulping process involves pulping at 3000 rpm to 4500 rpm for 120 to 200 minutes.
[0011] The solid halide material is one or a mixture of at least two of the following: magnesium aluminum hydrotalcite, tricalcium aluminate (C3A), tricalcium silicate, calcium oxide, aluminum oxide, aluminum silicate, metakaolin, and fly ash.
[0012] The adhesive is one or a mixture of at least two of the following: polytetrafluoroethylene, styrene-butadiene rubber, polyacrylic acid, polyacrylonitrile, sodium alginate, polyvinyl alcohol, and polyethylene oxide.
[0013] The dispersant is one or a mixture of at least two of sodium carboxymethyl cellulose, sodium hexadecylbenzene sulfonate, and polyacrylic acid block polymer (molecular weight 2000-5500).
[0014] The wetting agent is a nonionic surfactant.
[0015] The nonionic surfactant is one or a mixture of at least two of the following: polyether-modified siloxane, fatty alcohol polyether, and oxyethylene alkylphenol ether.
[0016] The water is deionized water.
[0017] In a preferred embodiment, in step S02,
[0018] The coating thickness is 1μm to 7μm.
[0019] The coating is applied to one side only.
[0020] The base film is a PP base film, a glass fiber base film, or a PE base film.
[0021] The baking temperature is 45℃~75℃, and the coating speed during baking is 2m / min~7m / min; the temperature is increased incrementally, and the gradient range of the increase is 5℃~15℃.
[0022] In this embodiment, baking is carried out in a coating oven, which has multiple sections, each with its own freely adjustable temperature. This application sets incremental temperature values based on the number of oven sections to achieve coating and baking. Taking a 7-section oven as an example: the baking temperature of the first section is 45°C, then from the first to the seventh section, the temperature of each section increases by 5°C compared to the previous section, reaching 75°C for the seventh section. Furthermore, this embodiment also provides an ion battery separator prepared by the above-described method.
[0023] In another aspect, embodiments of the present invention also provide the application of the ion battery separator, which can be used in an ion battery, and the slurry coating surface of the ion battery separator is disposed close to the negative electrode of the ion battery.
[0024] When the ion battery separator is applied to an ion battery, the ion battery separator can be coated on both sides with a total coating thickness of ≤6μm. One side of the separator (the side near the positive electrode) is coated with adhesive (PVDF or PMMA), and the other side (the side near the negative electrode) is coated with the slurry to improve the liquid retention capacity of the separator.
[0025] The negative electrode of the ion battery is prepared using a metal halide-graphite intercalation compound.
[0026] The metal halide is one of metal chloride, metal fluoride, metal bromide or metal iodide.
[0027] The ion battery is one of lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, aluminum-ion batteries, or lithium-sulfur batteries.
[0028] This application utilizes a slurry coating applied to a base film and controls the proportions of its components. This allows the slurry coating to interact with the negative electrode of the ion battery (prepared using a metal halide-graphite intercalation compound) (modification and synergy), effectively immobilizing halides and halide ions during cycling. This prevents halides and halide ions from shuttling through the electrolyte, thus effectively avoiding damage to the base film caused by halide ions and other side reactions. Consequently, it effectively prevents problems such as yellowing of the base film, decreased electrochemical stability, and reduced thermal shrinkage, effectively improving and ensuring the cycling performance of the negative electrode. The preparation process of this application is simple, easy to operate, low-cost, and quick, making it suitable for large-scale industrial production. Detailed Implementation
[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0030] It should be noted that if the embodiments of the present invention involve directional indicators (such as up, down, left, right, front, back, top, bottom, etc.), the directional indicators are only used to explain the relative positional relationship and movement of the components in a specific posture. If the specific posture changes, the directional indicators will also change accordingly.
[0031] In this application, unless otherwise expressly specified and limited, the terms "installation," "connection," "joining," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components, unless otherwise expressly limited. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific circumstances.
[0032] It should be noted that when a component is described as "fixed to" or "set on" another component, it can be directly on the other component or there may be an intervening component. When a component is described as "connected to" another component, it can be directly connected to the other component or there may be an intervening component.
[0033] Furthermore, if the embodiments of this invention involve descriptions such as "first" or "second," these descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined with "first" or "second" may explicitly or implicitly include at least one of those features. Additionally, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. If the combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by this invention.
[0034] Example 1
[0035] A method for preparing an ion battery separator includes the following steps:
[0036] S01. Mix 45% solid mixture and 55% water to obtain a slurry; the solid mixture comprises the following components based on 100% by mass: 96% solid material, 3% binder, 0.2% dispersant and 0.8% wetting agent; the percentages are by mass.
[0037] S02. The slurry from step S01 is applied to the base membrane and baked to obtain the ion battery separator.
[0038] In step S01,
[0039] The solid mixture was mixed at 500 rpm for 40 min.
[0040] The pulping process was performed at 3000 rpm for 200 minutes.
[0041] The solid halide material is magnesium aluminum hydrotalcite.
[0042] The adhesive is polytetrafluoroethylene.
[0043] The dispersant is sodium carboxymethyl cellulose.
[0044] The wetting agent is a nonionic surfactant, which is a polyether-modified siloxane.
[0045] The water is deionized water.
[0046] In step S02,
[0047] The coating thickness is 1 μm.
[0048] The coating is applied to one side only.
[0049] The base film is a PP base film.
[0050] The baking temperature is 45℃~75℃, and the coating speed during baking is 3m / min; the temperature is increased incrementally, and the gradient range of the increase is 5℃.
[0051] The ion battery separator can be used in ion batteries, and the slurry coating surface of the ion battery separator is located close to the negative electrode of the ion battery.
[0052] When the ion battery separator is applied to an ion battery, the ion battery separator can be coated on both sides with a total coating thickness of 6 μm. One side of the separator (the side closer to the positive electrode) is coated with PVDF, and the other side (the side closer to the negative electrode) is coated with the slurry to improve the liquid retention capacity of the separator.
[0053] The negative electrode of the ion battery is prepared using a metal halide-graphite intercalation compound.
[0054] The metal halide is a metal chloride; the ion battery is a lithium-ion battery.
[0055] Example 2
[0056] A method for preparing an ion battery separator includes the following steps:
[0057] S01. Mix 30% of the solid mixture and 70% of water to obtain a slurry; the solid mixture comprises the following components based on 100% by mass: 94% solid material, 5% binder, 0.5% dispersant and 0.5% wetting agent; the percentages are by mass.
[0058] S02. The slurry from step S01 is applied to the base membrane and baked to obtain the ion battery separator.
[0059] In step S01,
[0060] The solid mixture was mixed at 1000 rpm for 20 min.
[0061] The pulping process was performed at 4500 rpm for 120 minutes.
[0062] The solid halogen material is tricalcium silicate.
[0063] The adhesive is styrene-butadiene rubber.
[0064] The dispersant is sodium hexadecylbenzenesulfonate.
[0065] The wetting agent is a nonionic surfactant, and the nonionic surfactant is a fatty alcohol polyether.
[0066] The water is deionized water.
[0067] In step S02,
[0068] The coating thickness is 4 μm.
[0069] The coating is applied to one side only.
[0070] The base film is a glass fiber base film.
[0071] The baking temperature is 45℃~75℃, and the coating speed during baking is 3.5m / min; the temperature is increased incrementally, and the incremental gradient range is 10℃.
[0072] The ion battery separator can be used in ion batteries, and the slurry coating surface of the ion battery separator is located close to the negative electrode of the ion battery.
[0073] When the ion battery separator is applied to an ion battery, the ion battery separator can be coated on both sides with a total coating thickness of 6 μm. One side of the separator (the side closer to the positive electrode) is coated with PMMA, and the other side (the side closer to the negative electrode) is coated with the slurry to improve the liquid retention capacity of the separator.
[0074] The negative electrode of the ion battery is prepared using a metal halide-graphite intercalation compound.
[0075] The metal halide is a metal fluoride; the ion battery is a lithium-ion battery.
[0076] Example 3
[0077] A method for preparing an ion battery separator includes the following steps:
[0078] S01. Mix 15% solid mixture and 85% water to obtain a slurry; based on the mass of the solid mixture as 100%, the solid mixture comprises the following components: 90% solid material, 8% binder, 1% dispersant and 1% wetting agent; the percentages are by mass.
[0079] S02. The slurry from step S01 is applied to the base membrane and baked to obtain the ion battery separator.
[0080] In step S01,
[0081] The solid mixture was mixed at 700 rpm for 30 min.
[0082] The pulping process was carried out at 3500 rpm for 160 minutes.
[0083] The solid halogen material is calcium oxide.
[0084] The adhesive is polyacrylic acid.
[0085] The dispersant is sodium carboxymethyl cellulose.
[0086] The wetting agent is a nonionic surfactant, and the nonionic surfactant is an oxyethylene alkylphenol ether.
[0087] The water is deionized water.
[0088] In step S02,
[0089] The coating thickness is 5 μm.
[0090] The coating is applied to one side only.
[0091] The base film is a PE base film.
[0092] The baking temperature is 45℃~75℃, and the coating speed during baking is 2m / min; the temperature is increased incrementally, and the gradient range of the increase is 15℃.
[0093] The ion battery separator can be used in ion batteries, and the slurry coating surface of the ion battery separator is located close to the negative electrode of the ion battery.
[0094] When the ion battery separator is applied to an ion battery, the ion battery separator can be coated on both sides with a total coating thickness of 6 μm. One side of the separator (the side closer to the positive electrode) is coated with PVDF, and the other side (the side closer to the negative electrode) is coated with the slurry to improve the liquid retention capacity of the separator.
[0095] The negative electrode of the ion battery is prepared using a metal halide-graphite intercalation compound.
[0096] The metal halide is a metal bromide, and the ion battery is a lithium-ion battery.
[0097] Example 4
[0098] A method for preparing an ion battery separator includes the following steps:
[0099] S01. Mix 35% solid mixture and 65% water to obtain a slurry; the solid mixture comprises the following components based on 100% by mass: 96% solid material, 3% binder, 0.6% dispersant and 0.4% wetting agent; the percentages are by mass.
[0100] S02. The slurry from step S01 is applied to the base membrane and baked to obtain the ion battery separator.
[0101] In step S01,
[0102] The solid mixture was mixed at 800 rpm for 35 min.
[0103] The pulping process was performed at 4000 rpm for 150 minutes.
[0104] The solidified brine material is metakaolin.
[0105] The adhesive is polyvinyl alcohol.
[0106] The dispersant is sodium carboxymethyl cellulose.
[0107] The wetting agent is a nonionic surfactant, which is a polyether-modified siloxane.
[0108] The water is deionized water.
[0109] In step S02,
[0110] The coating thickness is 3 μm.
[0111] The coating is applied to one side only.
[0112] The base film is a PP base film.
[0113] The baking temperature is 45℃~75℃, and the coating speed during baking is 7m / min; the temperature is increased incrementally, and the gradient range of the increase is 5℃.
[0114] The ion battery separator can be used in ion batteries, and the slurry coating surface of the ion battery separator is located close to the negative electrode of the ion battery.
[0115] When the ion battery separator is applied to an ion battery, the ion battery separator can be coated on both sides with a total coating thickness of 6 μm. One side of the separator (the side closer to the positive electrode) is coated with PMMA, and the other side (the side closer to the negative electrode) is coated with the slurry to improve the liquid retention capacity of the separator.
[0116] The negative electrode of the ion battery is prepared using a metal halide-graphite intercalation compound.
[0117] The metal halide is a metal iodide; the ion battery is a lithium-ion battery.
[0118] Comparative Example 1
[0119] A method for preparing an ion battery separator includes the following steps:
[0120] PVDF is uniformly coated on both sides of the PP base film. The PVDF coating thickness on one side of the PP base film (the side closer to the positive electrode) is 5 μm, and the PVDF coating thickness on the other side (the side closer to the negative electrode) is 1 μm. After baking, the ion battery separator is obtained.
[0121] The baking temperature is 45℃~75℃, and the coating speed during baking is 3m / min; the temperature is increased incrementally, and the gradient range of the increase is 5℃.
[0122] The ion battery separator is used in an ion battery; the negative electrode of the ion battery is prepared using a metal halide-graphite intercalation compound. The metal halide is a metal chloride; the ion battery is a lithium-ion battery.
[0123] Experiments revealed that when the ion battery separators prepared in Examples 1 to 4 were applied to ion batteries, no halides or halide ions were observed shuttling in the electrolyte. After prolonged use, the base film did not yellow, exhibiting good electrochemical stability, good thermal shrinkage, and maintained good cycle performance of the negative electrode. In contrast, the ion battery separator of Example 1 showed a large number of halides and halide ions shuttling in the electrolyte. After prolonged use, the base film yellowed, its electrochemical stability deteriorated, and its thermal shrinkage decreased, leading to poorer cycle performance and even failure.
[0124] In the description of this specification, references to terms such as "an embodiment," "example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example.
[0125] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style of the specification is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
[0126] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An application of an ion battery separator, characterized in that, The ion battery separator is used in an ion battery, and the slurry coating surface of the ion battery separator is located close to the negative electrode of the ion battery. The negative electrode of the ion battery is prepared using a metal halide-graphite intercalation compound. The method for preparing the ion battery separator includes the following steps: S01. Based on the mass of the slurry, 15%–45% of the solid mixture and 55%–85% of the water are mixed and pulped to obtain the slurry; based on the mass of the solid mixture, the solid mixture comprises the following components: 90%–96% solid materials, 3%–8% binder, 0.2%–1% dispersant and 0.2%–1% wetting agent; S02. The slurry from step S01 is applied to the base film and baked to obtain the ion battery separator.
2. The application of the ion battery separator according to claim 1, characterized in that, In step S01, the solid mixture is mixed at 500 rpm to 1000 rpm for 20 min to 40 min; The pulping process involves pulping at 3000 rpm to 4500 rpm for 120 min to 200 min.
3. The application of the ion battery separator according to claim 2, characterized in that, In step S01, the solid halide material is one or a mixture of at least two of the following: magnesium aluminum hydrotalcite, tricalcium aluminate, tricalcium silicate, calcium oxide, aluminum oxide, aluminum silicate, metakaolin, and fly ash. The adhesive is one or a mixture of at least two of the following: polytetrafluoroethylene, styrene-butadiene rubber, polyacrylic acid, polyacrylonitrile, sodium alginate, polyvinyl alcohol, and polyethylene oxide.
4. The application of the ion battery separator according to claim 3, characterized in that, In step S01, the dispersant is one or a mixture of at least two of sodium carboxymethyl cellulose, sodium hexadecylbenzene sulfonate, and polyacrylic acid block polymer.
5. The application of the ion battery separator according to claim 4, characterized in that, In step S01, the wetting agent is a nonionic surfactant; the nonionic surfactant is one or a mixture of at least two of polyether-modified siloxane, fatty alcohol polyether, and oxyethylene alkylphenol ether. The water is deionized water.
6. The application of the ion battery separator according to claim 1, characterized in that, In step S02, the coating thickness is 1μm to 7μm; the coating is a single-sided coating; and the base film is a PP base film, a glass fiber base film, or a PE base film.
7. The application of the ion battery separator according to claim 6, characterized in that, In step S02, the baking temperature is 45℃~75℃, the coating speed during baking is 2m / min~7m / min, and the temperature is increased incrementally, with an increment range of 5℃~15℃.
8. The application of the ion battery separator according to claim 1, characterized in that, The metal halide is one of metal chloride, metal fluoride, metal bromide or metal iodide; The ion battery is one of lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, aluminum-ion batteries, or lithium-sulfur batteries.
9. An ion battery, characterized in that, It includes a negative electrode and a separator for an ion battery; the negative electrode of the ion battery is prepared using a metal halide-graphite intercalation compound; the separator for the ion battery is prepared by the preparation method described in any one of claims 1 to 8.
Citation Information
Patent Citations
Sticky diaphragm for power battery and its preparation method
CN108039440A
Lithium-sulfur battery composite coating diaphragm as well as preparation method and application thereof
CN111725467A
